Sunday

March 1, 2015

March 1, 2015

Posted by **Ant** on Thursday, June 13, 2013 at 10:06pm.

(x - y - 1)3 = x; (1, -1)

y =

- Calculus -
**Steve**, Friday, June 14, 2013 at 12:04amy+1 = -1/f'(1) (x-1)

3(x-y-1)^2 (1-y') = 1

at (1,-1)

-3(1-y') = 1

y' = 4/3

**Answer this Question**

**Related Questions**

Calculus - Find an equation of the tangent line to the graph of the function f ...

Calculus 2nd Post please help - Find an equation of the tangent line to the ...

Calculus - 1. Given the function f defined by f(x) = x^3-x^2-4X+4 a. Find the ...

calculus - Use the function defined below to find an equation of the tangent ...

Calculus - Functions? - #1. A cubic polynomial function f is defined by f(x) = ...

CALCULUS HELP - Write the equation of the tangent line to the graph of the ...

Calculus - Given the function defined as f(x)=x^3-(3/2)x^2-6x+10 a) Explain why ...

Calculus - Given the function defined as f(x)=x^3-(3/2)x^2-6x+10 a) Explain why ...

calculus - 1. Which of the following expressions is the definition of the ...

Calculus - 1. a) For the Function and point below , Find f’(a). b) Determine ...